Comparison of Ethylene/1-Hexene Copolymers Microstructures Synthesized by Homogeneous and Heterogeneous Metallocene Catalysts - Saeid Ahmadjo (علوم و تکنولوژی پلیمر, 2013)
The substituted (bis-2-PhIndZrCl2) and non-substituted (bis-IndZrCl2) indenylbased metallocene catalysts were synthesized and used in homogenous and heterogeneous forms for copolymerization of ethylene and 1-hexene. The MCM-41 nano silica was used as support in heterogenization of the catalysts. The substituted (bis-2-PhIndZrCl2) metallocene catalyst in homogenous and heterogeneous forms showed lower activities in comparison to non-substituted (bis-IndZrCl2) metallocene catalyst. The microstructures of the obtained copolymers were investigated by techniques such as DSC, CNMR and TRRF. The kinetic study showed that the decay index (DI) was decreased for both homogeneous catalysts due to unstable kinetic behaviors. However, the decay index contents approached one, using heterogeneous forms of catalyst which was an indication of stable kinetic behaviors. The kinetic results also displayed negative effect on the catalysts activities both in the homogeneous and heterogeneous forms by addition of comonomer on the polymerization. The triad distributions of obtained polymer by NMR technique exhibited the higher ratio of EEH, EHE, EEE triads than the other triads. The comonomer incorporationacceptability of substituted metallocene catalyst (bis-2-PhIndZrCl2) was higher than non-substituted catalyst (bis-IndZrCl2) as its comonomer acceptability increased from 1.3% to 5.4% by substitution mechanism. Microstructures of copolymers obtained by supported metallocene catalyst showed more non-uniform comonomer distribution in comparison with unsupported catalyst. The lamella thickness distributions for polymer obtained by supported substituted metallocene catalyst (bis-2-PhIndZrCl2) were in the ranges (3-8 ). However, for supported metallocene non-substituted catalysts (bis-IndZrCl2) the lamella thickness were in the ranges (3-16 ).